Low hemoglobin is associated with postoperative cerebral infarction in moyamoya disease: development of a predictive model based on low hemoglobin - Wu, Haitao; Wang, Tingxuan; Li, Fangbao; Bao, Yue; Lu, Bin; Li, Luo (Frontiers in Neurology, 2025)
BackgroundAnemia is considered a risk factor for cardiovascular disease. However, there is little evidence regarding the relationship between hemoglobin (HB) and cerebral infarction after revascularization in patients with moyamoya disease (MMD). This study aimed to explore the relationship between postoperative cerebral infarction and HB in patients with MMD and to establish a predictive model.MethodsDemographic information and different HB levels (the preoperative and postoperative HB, highest and lowest HB, and mean HB during hospitalization) of 112 patients with MMD were collected, of which 11 had cerebral infarction after revascularization.ResultsIn the binomial logistic regression analysis, low HB levels were an independent risk factor for cerebral infarction after revascularization, which also led to a worse long-term prognosis in patients with MMD. The risk factors, including Pre-HB, Post-HB, type of MMD, and hypertension (HTN), were incorporated into the receiver operating characteristic curve, which yielded an area under the curve (AUC) of 0.83.ConclusionThe prediction model was visualized using a nomogram, and a clinical decision curve was drawn to evaluate the net benefit of clinical decisions.